2007
DOI: 10.1038/nrn2175
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in brain tumours

Abstract: Despite aggressive surgery, radiotherapy and chemotherapy, malignant gliomas remain uniformly fatal. To progress, these tumours stimulate the formation of new blood vessels through processes driven primarily by vascular endothelial growth factor (VEGF). However, the resulting vessels are structurally and functionally abnormal, and contribute to a hostile microenvironment (low oxygen tension and high interstitial fluid pressure) that selects for a more malignant phenotype with increased morbidity and mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
1,064
5
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,225 publications
(1,136 citation statements)
references
References 135 publications
28
1,064
5
16
Order By: Relevance
“…To the best of our knowledge, this is the first study to characterize the vascular phenotype of a mouse brain tumor model with mMRI. We showed that (Jain et al, 2007;Vajkoczy and Menger, 2000). Our results also show characteristic differences between the vasculatures of D12 and D17 tumors.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to characterize the vascular phenotype of a mouse brain tumor model with mMRI. We showed that (Jain et al, 2007;Vajkoczy and Menger, 2000). Our results also show characteristic differences between the vasculatures of D12 and D17 tumors.…”
Section: Discussionsupporting
confidence: 73%
“…Knowledge of the three-dimensional (3D) architecture of blood vessels is crucial for several reasons: (1) Various neuropathologies ranging from Alzheimer's disease to brain tumors involve anomalous blood vessels (Iadecola, 2004;Jain et al, 2007). (2) The physiologic basis of image contrast in functional magnetic resonance imaging critically depends on the underlying microvasculature (Moonen et al, 1990;Pathak et al, 2003Pathak et al, , 2008c.…”
Section: Introductionmentioning
confidence: 99%
“…Vasculogenesis was traditionally considered an embryonic process but has since been identified to occur in several tumor types (Lyden et al, 2001) including brain tumors (SantarelLi et al, 2006;Zhang et al, 2009). Vasculogenesis involves the de novo formation of blood vessels that utilize bone marrow-derived endothelial progenitor cells (Jain et al, 2007). Angiogenesis is the production of new blood vessels by endothelial cells from pre-existing vessels and is considered to be the primary mode of vessel formation in gliomas (Tate and Aghi, 2009).…”
Section: Brain Tumor Stem-like Cellsmentioning
confidence: 99%
“…GSC maintenance and fate rely upon external regulatory interactions with the brain microenvironment, of which vascular niche is thought to play a critical role [13]. Indeed, both the proximity to capillaries and pro-angiogenic activity of GSCs suggest the existence of crucial communication pathways between these cells and the endothelium [14,15]. …”
Section: Introductionmentioning
confidence: 99%